Gene mutations and treatment outcome in chronic lymphocytic leukemia: results from the CLL8 trial - Stilgenbauer, Stephan; Schnaiter, Andrea Barbara; Paschka, Peter; Zenz, Thorsten; Rossi, Marianna; Döhner, Konstanze; Bühler, Andreas; Böttcher, Sebastian; Ritgen, Matthias; Kneba, Michael; Winkler, Dirk; Tausch, Eugen; et al. (Blood, 2014)
Key Points. Independent prognostic impact of biological markers, notably TP53 and SF3B1 mutations, in CLL patients requiring therapy.NOTCH1 mutation as a predictive factor for reducedbenefit from the addition ofrituximab to FC chemotherapy.
Gesehen am 17.08.2020